The influence of personality traits and coping strategies on the quality of life of patients with relapsing-remitting type of multiple sclerosis - Krstić, Dragan; Krstić, Zvezdana D.; Stojanović, Zvezdana; Kolundžija, Ksenija; Stojković, Mirjana; Dinčić, Evica (Vojnosanitetski pregled, 2021)
Background/Aim. Multiple sclerosis (MS) is a chronic, progressive autoimmune disease of the central nervous system, that can reduce quality of life. Personality traits and coping strategies are significant factors in interpersonal variance regarding quality of life. The aim of this study was to examine relations between personality traits and coping strategies in patients with relapsing-remitting (RR) type of MS, and to examine relations of personality traits, coping strategies, and quality of life in patients with RR type of MS. Methods. This observational cross-sectional study included 66 patients (34 female, 32 male) with clinically definitive MS, based on the McDonald criteria. The following clinical scales were used to examine personality traits, coping strategies, and quality of life: Revised NEO Personality Inventory (NEO-PI-R), Coping Strategies Inventory (CSI), and Multiple Sclerosis Quality of Life (MSQOsL-54). Results. The average age of the patients was 41.6 ± 7.1 years. The Pearsonʼs correlation coefficient showed that with regards to coping strategies, the only positive correlation existed with neuroticism (r = 0.502). The correlation was negative between neuroticism and physical (r = -0.284, p < 0.05) and mental health (r = -0.289, p < 0.05), as well as between passive coping strategies and mental health (r = -0.358, p < 0.05), meaning that the patients with a higher level of neuroticism, and who relied on passive coping strategies, had a lower quality of life. Conclusion: This research showed the importance of personality traits and coping strategy assessment in patients with RR-type MS. Participation in cognitive-behavioral therapy, with emphasis on active coping strategies, can improve the quality of life in patients with MS.
Keywords: adaptation, physiological; multiple sclerosis; personality; recurrence; quality of life; serbia; stress, psychological; surveys and questionnaires